The Effect of Using Vancomycin Powder and Betadine for Skin Preparation in the Prevention of Wound Infection in Grades I and II Open Fractures of the Lower Limb: A Double-Blind Clinical Trial - yaser Abolhosni; Mohsen Absalan; Mohammadali Zakeri; Sohila Bakhtiari (Iranian South Medical Journal)
Background: Skin preparation in the operating room is important to prevent infection after open fracture surgery. The present study was conducted with the aim of investigating the effect of the simultaneous use of betadine and vancomycin powder for the preparation of damaged skin in preventing wound infection in open fractures of the lower limb undergoing internal fixation surgery. Materials and Methods: The present study was a double-blind clinical trial on 40 men with open fractures of the lower limb who underwent open reduction surgery and internal fixation. Patients were randomly divided into control and intervention groups. In order to prepare the damaged skin before surgery, betadine 10% was used in the control group and betadine 10% plus 2 grams of vancomycin powder in the intervention group. Open wounds caused by the removal of bone from the skin and surgical incisions within 30 days (days 1, 2, 14 and 30) after surgery were scored in terms of infection using the ASEPSIS scoring method. The results were analyzed in SPSS 22 software (p<0.05). Results: There was no significant difference between the two groups in terms of mean age, duration of emergency hospitalization until surgery, height, weight and body mass index, marital status, fracture grade, bleeding rate, wound infection score and surgery duration (p>0.05). Conclusion: The simultaneous use of betadine and vancomycin powder has no effect on wound infection after open reduction surgery and internal fixation in patients with open lower limb fractures.